Divergent effects of single and combined stress of drought and salinity on the physiological traits and soil properties of Platycladus orientalis saplings - Li, Shan; Lu, Sen; Wang, Jing; Liu, Zepeng; Yuan, Chuhuan; Wang, Min; Guo, Junkang (Frontiers in Plant Science, 2024)
Drought and salinity are two abiotic stresses that affect plant productivity. We exposed 2-year-old Platycladus orientalis saplings to single and combined stress of drought and salinity. Subsequently, the responses of physiological traits and soil properties were investigated. Biochemical traits such as leaf and root phytohormone content significantly increased under most stress conditions. Single drought stress resulted in significantly decreased nonstructural carbohydrate (NSC) content in stems and roots, while single salt stress and combined stress resulted in diverse response of NSC content. Xylem water potential of P. orientalis decreased significantly under both single drought and single salt stress, as well as the combined stress. Under the combined stress of drought and severe salt, xylem hydraulic conductivity significantly decreased while NSC content was unaffected, demonstrating that the risk of xylem hydraulic failure may be greater than carbon starvation. The tracheid lumen diameter and the tracheid double wall thickness of root and stem xylem was hardly affected by any stress, except for the stem tracheid lumen diameter, which was significantly increased under the combined stress. Soil ammonium nitrogen, nitrate nitrogen and available potassium content was only significantly affected by single salt stress, while soil available phosphorus content was not affected by any stress. Single drought stress had a stronger effect on the alpha diversity of rhizobacteria communities, and single salt stress had a stronger effect on soil nutrient availability, while combined stress showed relatively limited effect on these soil properties. Regarding physiological traits, responses of P. orientalis saplings under single and combined stress of drought and salt were diverse, and effects of combined stress could not be directly extrapolated from any single stress. Compared to single stress, the effect of combined stress on phytohormone content and hydraulic traits was negative to P. orientalis saplings, while the combined stress offset the negative effects of single drought stress on NSC content. Our study provided more comprehensive information on the response of the physiological traits and soil properties of P. orientalis saplings under single and combined stress of drought and salt, which would be helpful to understand the adapting mechanism of woody plants to abiotic stress.